Urban Leisure and the Rise of Commercial Entertainment in 19th-Century Vilnius: The Role of Ivan Shuman in a Modernizing City - Paškauskas, Juozapas (Lietuvos istorijos studijos, 2024)
The article explores the evolution of the entertainment scene in Vilnius during the second half of the 19th century, focusing on its marginal position outside national canons and mainstream theatre. Through the work of Ivan Antonovich Shuman, the city’s first entertainment entrepreneur, the study situates Vilnius’ post-serfdom and post-uprising entertainment culture within a broader regional context. It highlights how this emerging culture intersected with the modernization challenges of the time, particularly the demand for public urban spaces. This development reflected the rise of a new urban culture and its consumers, who crossed traditional socio-economic boundaries.
Keywords: Russian Empire; Vilnius; leisure; commercialization; urbanization; Ivan Antonovich Shuman